2010
DOI: 10.1007/s00464-010-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after laparoscopic adrenalectomy

Abstract: The morbidity and mortality rates after LA are low. Dependent functional status and peripheral vascular disease predispose to postoperative morbidity. Dependent status, higher ASA class, and respiratory and neurologic comorbidities are associated with longer operative time and LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 36 publications
5
32
0
1
Order By: Relevance
“…In fact, the largest institutional studies have demonstrated a mortality and morbility rate of 6.7-6.8 and 0.27-0.5% respectively [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the largest institutional studies have demonstrated a mortality and morbility rate of 6.7-6.8 and 0.27-0.5% respectively [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary imaging techniques with an increased detection of adrenal incidentalomas and new surgical techniques with reduction of morbidity and mortality with endoscopic methods [1, 2] have contributed to the increase in operations. In 1992, Gagner et al were among the first to describe laparoscopic adrenalectomy [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the number of adrenalectomies has increased considerably due to improved diagnostic methods and the introduction of the laparoscopic adrenalectomy technique, which has emerged as a safer surgical procedure and reduced the incidence of post-surgical complications (Kaye et al, 2010;Gupta et al, 2011). In 2006, more than 5000 patients were submitted to adrenalectomy in the United States only and around 40% of these surgeries were performed in men (Kaye et al, 2010;Gupta et al, 2011). Despite the efforts to keep the exogenous adrenal steroid administration at physiological levels, under-or over-dosing are frequent events in ADX patients and associated with a higher incidence of post-surgical side effects and co-morbidities (Kaye et al, 2010).…”
Section: (H) (I) (C) (F) (D) (G)mentioning
confidence: 99%
“…In the last decade, laparoscopic adrenalectomy has become a 'state of the art' technique for the surgical treatment of many conditions requiring the removal of adrenal glands in humans, such as pheochromocytoma and adrenal hyperplasia secondary to Cushing's disease, with more than 5000 surgeries performed in 2006 in the United States only (Gupta et al, 2011). Very little is known on the reproductive outcomes of this surgical procedure, which further requires steroid hormone replacement for a life-time.…”
Section: Introductionmentioning
confidence: 99%